ANALISA PERBANDINGAN OBAT ANTIHIPERTENSI (OHT) DENGAN KEJADIAN POLA TEKANAN DARAH NONDIPPERS PADA PENDERITA HIPERTENSI TANPA STROK ISKEMIK - Rachman, Mochammad Erwin; Kaelan, Cahyono (Fakultas Farmasi UMI, 2014)
The pattern of blood pressure hypertensive nondippers is one of the factors that increase the risk of suffering from cardiovascular and cerebrovascular disorders , but the effect of antihypertensive drugs work period ( OHT ) relating to the type of the pattern of blood pressure in patients with hypertension hypertensive nondippers still not widely studied . This study aims to analyze the working relationship with the incidence pattern of antihypertensive drug blood pressure hypertension nondippers in patients with post- acute stroke ischemic stroke with and without hypertension . The method used was a cross -sectional study with 60 samples ( 30 hypertensive patients with ischemic stroke and 30 patients with hypertension as a control ) of the Hospital Dr . WahidinSudirohusodo Makassar and its network in 2013 . The results showed chi-square test patterns obtained blood pressure in hypertensive nondippers larger user group types ACEI captopril group OAH 18 ( 94.7 % ) with grades ( p > 0.05 ) with OR = 4.6 . It can be concluded that there are patterns of blood pressure hypertension incidence nondippers against ischemic stroke incidence was greater in OHT group ACEI types captopril group , although not significantly.